Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

If f(x) = 5x - 2 and g(x) = 1 - 2x, find (fg)(x).I am not sure if my answer is right please help me

If Fx 5x 2 And Gx 1 2x Find FgxI Am Not Sure If My Answer Is Right Please Help Me class=

Sagot :

Given:

f(x) = 5x - 2

g(x) = 1 - 2x

Let's find (fg)(x).

To solve the function operation, we have:

(fg)(x) = f(x) * g(x)

Thus, we have:

[tex](fg)(x)=(5x-2)(1-2x)[/tex]

Solving further:

Expand using FOIL method, then apply distributive property

[tex]\begin{gathered} (fg)(x)=5x(1-2x)-2(1-2x) \\ \\ (fg)(x)=5x(1)+5x(-2x)-2(1)-2(-2x)_{} \\ \\ (fg)(x)=5x-10x^2-2+4x \\ \\ (fg)(x)=+5x+4x-10x^2-2 \\ \\ (fg)(x)=9x-10x^2-2^{} \end{gathered}[/tex]

ANSWER:

[tex]9x-10x^2-2^{}[/tex]